Proposal of a methodological approach for creative pedagogies concerning issues of sustainable development - Vergara-Romero, Arnaldo (2023)
In this talk, we will discuss a methodological proposal for addressing education for sustainable development using creative pedagogies. The primary purpose is to establish a technique that uses art as a connection between learning and creativity, so allowing students to acquire skills connected to sustainability in a variety of scientific subjects. Students engage in experiential learning and their ability to think critically when given the opportunity to interact with works of art. The presentation emphasizes that education for sustainability is not restricted to instruction in ecology alone; rather, it also encompasses a vision of the future and a shift in the way that researching and modeling the future is done. The methodological proposal is broken down into various steps, the first of which is the diagnosis of the problem. Students are encouraged to select a contemporary artistic expression that addresses concerns pertaining to sustainability, and then to compose an analytical essay regarding both the artistic expression and its connection to the subject matter that is being researched. In the context of an exhibition, these articles would be presented in conjunction with the pieces of art that were chosen. The presentation refers to several studies and pieces of research that are associated with education for sustainability, creative pedagogy, and the use of art in the classroom. The fields of research that focus on social learning, human-environment integration, environmental management, and the assessment of sustainability are highlighted.